2015
DOI: 10.1590/0037-8682-0242-2015
|View full text |Cite
|
Sign up to set email alerts
|

Venomous and poisonous arthropods: identification, clinical manifestations of envenomation, and treatments used in human injuries

Abstract: This review presents the main species of venomous and poisonous arthropods, with commentary on the clinical manifestations provoked by the toxins and therapeutic measures used to treat human envenomations. The groups of arthopods discussed include the class Arachnida (spiders and scorpions, which are responsible for many injuries reported worldwide, including Brazil); the subphylum Myriapoda, with the classes Chilopoda and Diplopoda (centipedes and millipedes); and the subphylum Hexapoda, with the class Insect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 10 publications
1
22
0
1
Order By: Relevance
“…The present study demonstrated that DqV inhibits the nociceptive behavior and the number of polymorphonuclear leukocytes at the inflammatory stage of the healing process, corroborating the popular use in inflammatory and painful conditions (Haddad et al, 2015).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The present study demonstrated that DqV inhibits the nociceptive behavior and the number of polymorphonuclear leukocytes at the inflammatory stage of the healing process, corroborating the popular use in inflammatory and painful conditions (Haddad et al, 2015).…”
Section: Resultssupporting
confidence: 85%
“…In Brazilian folk medicine, ants belonging to the genus Dinoponera (Formicidae: Ponerinae) are used to treat inflammatory conditions: the ant sting for rheumatism by indigenous population (Haddad Junior, Amorim, Haddad Junior, & Cardoso, 2015) and the macerate of the entire ant for ear ache (Costa Neto, 2011). The venom gland in the sting apparatus of Dinoponera quadriceps produces a venom that contains Dinoponera toxins (DnTxs), pilosulin-like toxins, ICK-folded toxins, lethal-like toxins, allergen proteins and esterases (phospholipases and carboxylesterases) Mariano et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For terrestrial envenomations, hot-water immersion was less commonly recommended (Table 5) [74,75,76,77,78], although there has been some support for the use of targeted, localized heat in the treatment of insect bites and stings [79]. Heat therapy is specifically contraindicated for recluse spider envenomations ( Loxoceles spp.…”
Section: Hot-water Immersion For Other Envenomationsmentioning
confidence: 99%
“…1 Some patients may present with systemic symptoms such as nausea, vomiting, and fever. 2 Treatment should be started with intensive washing of the affected area with soap and clean water to remove the pederin. 1,2 In established lesions, the use of potassium permanganate is helpful (1:40,000, or 1 tablet in 4 L of water) twice a day with cold wet compresses, corticosteroid creams, and oral antihistamines.…”
Section: Diagnosismentioning
confidence: 99%